Capitalizing on migration: The role of strong and weak ties among Peruvian entrepreneurs in the United States, Spain and Chile. (5th April 2017) - Paerregaard, Karsten
Abstract: How do Peruvian migrants use ethnic entrepreneurship to make headway in their countries of settlement? This article answers this question by using three ethnographic case studies to explore how Peruvian entrepreneurs mobilize resources to open restaurants in the United States, Spain and Chile. The finding is that Peruvian restaurant owners are adept in converting their educational skills and previous work experiences into human capital but that they often lack financial and cultural capital to establish new enterprises. Another insight is that while most Peruvian entrepreneurs use bonding capital to access these resources not all command enough bridging capital to capture customers outside their family and ethnic networks, which is critical to compete on the ethnic restaurant market. A final topic of inspection is the receiving contexts and the opportunity structures in the three countries and the way they facilitate or restrain immigrant entrepreneurships. The article concludes that migration scholars should inquire into the relations of inequality that the concepts of network and social capital gloss over and scrutinize how they shape the bonding and bridging capital immigrant entrepreneurs use to create mixed clienteles.